Pengaruh Influencer Endorsement dan Brand Trust Terhadap Minat Beli Produk Skincare Facetology pada Konsumen Miss Glam Panam - Venezia Pastika Ayusid; Meyzi Heryanto (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2025)
This study analyzes the effect of influencer endorsement and brand trust on the purchase intention of Facetology skincare products among consumers at Miss Glam Panam. The sample for this study consists of 96 respondents, using a quantitative method and data analysis performed using SPSS 27. The data analysis process includes several stages, such as validity testing, reliability testing, classical assumption testing, multiple linear regression testing, and coefficient of determination testing. Both influencer endorsement and brand trust have a positive and significant effect on purchase intention. Influencer endorsement holds the most dominant influence, with an R square value of 0.528 or 52.8%, where the likability dimension obtained the highest score. This means that the influencer's expertise in delivering product information using clear, easy-to-understand language, providing detailed information, and actively responding to consumers' questions makes the endorsement content more credible and increases purchase intention.